Study of Retinopathy and Microalbuminuria and Their Relation with Type 2 Diabetes Mellitus - Gupta, Niraj (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2024)
Diabetic retinopathy (DR) is a multifactorial microvascular complication of diabetes mellitus caused by damage to the blood vessels of the retina, the light-sensitive tissue located at the back of the eye. DR has been included by the World Health Organization in the priority list of eye diseases that can be partly prevented but not cured yet. Radiation retinopathy (RR) is a chronic and progressive condition that may result from exposure to any source of radiation, including external beam radiation, plaque brachytherapy, proton beam radiation, helium ion radiotherapy, and gamma knife radiotherapy. RR may be secondary to the treatment of intraocular tumors such as choroidal melanomas, retinoblastomas, and choroidal metastasis or from unavoidable exposure to excessive radiation from the treatment of cephalic, nasopharyngeal, orbital, and paranasal tumors among other malignancies. Microalbuminuria is a condition where a small amount of a protein called albumin is present in the urine. It can be a sign of kidney damage, especially in people with diabetes or high blood pressure. This review article summarizes study of DR, microalbuminuria, and type 2 diabetes mellitus and their correlation with each other.